(untitled) (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Dharmayasa IGNP, Sugiana IP, Anantanasakul P. 2025. Mangrove species distribution across soil texture gradients in Benoa Bay and Nusa Lembongan, Bali Province, Indonesia. Biodiversitas 26: 2908-2915. This study unveils the crucial role of mangrove ecosystems in enhancing coastal resilience and mitigating climate change through carbon sequestration and shoreline stabilization. This study identifies strong relationships between soil particle composition (sand, silt, clay, and gravel) and the distribution of mangrove species across five genera-dominated zones (Rhizophora, Sonneratia, Avicennia, Bruguiera, and Ceriops) in Bali, Indonesia. By establishing 20 plots at two sites, Benoa Bay and Nusa Lembongan, and quantitatively measuring stand structure (tree and sapling density, diameter, canopy cover, and Mangrove Health Index (MHI) and soil parameters (texture, pH, water content, bulk density, and total organic matter), this study revealed that Ceriops tagal dominates soils with 35-45% silt and clay content; Bruguiera gymnorrhiza thrives in sandy soils exceeding 60% sand; and Sonneratia alba is associated with substrates containing over 20% gravel. Principal component analysis and Pearson correlation reveal significant negative effects of gravel on canopy cover (r: -0.73, p<0.01) and MHI (r: -0.74, p<0.01), and a positive correlation between sand content and sapling density (r: 0.56, p<0.01). These findings not only underscore the critical role of soil texture in mangrove distribution and forest health but also emphasize the need to consider edaphic conditions in restoration and conservation strategies. This knowledge is vital for enhancing ecosystem sustainability and biodiversity.